Two Halves Make a Whole: Gender at the Crossroads of the Nigerian Development Agenda - Aina, Olabisi Idowu (Obafemi Awolowo University Press Limited, Ile- lfe, Nigeria, 2013)
The overarching effect of poverty across nations drew attention on gender inequality, a concept which has engaged the attention of scholars, development practitioners, policy makers, and civil society organisations for over three decades now. The continued existence of disparities between women and men in access and control over resources, and the overt discrimination against women throughout history, are not only seen as a clog in the wheel of national and international development agendas, importantly, the achievement of gender equality is bound up with all other goals of sustainable development, such as good governance, human rights, environmental sustainability, poverty reduction, and inclusiveness in development planning and practice. At the core of my work is presenting gender equality as a key element in the development process. Development is envisioned not just as a process of creating opportunities for individuals to earn sustainable livelihoods rather, it requires that men and women are able to operate within a conducive policy/social environment that allows them to seize those opportunities.